Education, fascism, memory, and the crisis of democracy in the 21st Century: Rethinking 9/11 - Giroux, Henry A. (Studia Krytyczne/Critical Studies, 2025)
This article examines the intersection of memory, militarism, and the rise of fascism in the United States in the aftermath of 9/11. It explores how the post-9/11 era, initially marked by national unity and solidarity, quickly devolved into militarism, xenophobia, and the erosion of civil liberties. The manipulation of collective memory and a regressive form of education have played a central role in the rise of far-right authoritarianism, with fear and historical amnesia fueling fascist politics. The commodification of loss and the disavowal of collective responsibility have undermined democracy, contributing to the current crisis of authoritarianism in America. Central to the fight against this authoritarian drift is the crucial notion of making education central to politics and the production of what might be called a radical democratic imaginary, which plays a vital role in shaping critically informed citizens. The article emphasizes that reclaiming educational spaces—both formal and cultural—as sites of critical inquiry and resistance is essential for resisting fascism and reimagining a democratic future.